Multispectral photodetectors based on 2D material/Cs3Bi2I9 heterostructures with high detectivity. (20th July 2021) - Zhang, Peng; Zhang, Yong; Wang, Wenhui; Gao, Lei; Li, Gefei; Zhang, Sheng; Lu, Junpeng; Yu, Yuanfang; Zhang, Jialin
Abstract: Group VA metal halide-based perovskites have emerged as intensively explored Pb-free perovskites, owing to their excellent environmental stability and low-toxicity. However, the relatively low carrier mobility and high photocarrier recombination rates restrict their applications in photodetectors. One promising approach to achieve higher performance is to integrate these Pb-free perovskites with 2D materials to form heterostructures. Here, we report on the high sensitivity photodetectors based on MoS2 /Cs3 Bi2 I9 and graphene/Cs3 Bi2 I9 heterostructures for multispectral regions. The heterostructures combine the high carrier mobility of 2D materials with superior light-harvesting properties of perovskites, as well as the effective built-in electric filed at the junction area, leading to efficient photocarrier separation and extraction. The specific detectivity of MoS2 /Cs3 Bi2 I9 device reaches 1.15 × 10 13 Jones for the detection of ultraviolet (UV) light of 325 nm, which is four orders of magnitude higher than UV detectors built on GaN. As a result of the efficient dark current suppression, the specific detectivity of graphene/Cs3 Bi2 I9 photodetector can be promoted to 5.24 × 10 11 Jones, 1.33 × 10 11 Jones, and 1.12 × 10 11 Jones for the detection of 325 nm, 447 nm, and 532 nm light, respectively.